2019
DOI: 10.1002/1873-3468.13458
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin promotes proliferation of neural stem cells from adult mouse spinal cord via the PI3K/AKT signaling pathway

Abstract: In this study, we tested the effect of melatonin on proliferation and differentiation of neural stem/progenitor cells (NSPCs) obtained from adult mouse spinal cord. We found that melatonin increases neurosphere formation from adult spinal cord NSPCs but does not alter the differentiation of the cells. Western blot results show that adult spinal cord NSPCs express both MT1 and MT2 melatonin receptors. The melatonin receptor antagonist 4P‐PDOT abrogates the melatonin‐induced neurosphere formation. Melatonin incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The most frequently observed signal transmission is that of the canonical ERK/MAPK pathway [19,107,[114][115][116]. Another repeatedly reported downstream pathway is that of PI3K/AKT signaling [20,27,88,112,117]. These findings are in line with those on programming of other stem cells, especially MSCs, as will be discussed in Section 8.…”
Section: Neurogenesis From Nscs/nspcssupporting
confidence: 65%
See 1 more Smart Citation
“…The most frequently observed signal transmission is that of the canonical ERK/MAPK pathway [19,107,[114][115][116]. Another repeatedly reported downstream pathway is that of PI3K/AKT signaling [20,27,88,112,117]. These findings are in line with those on programming of other stem cells, especially MSCs, as will be discussed in Section 8.…”
Section: Neurogenesis From Nscs/nspcssupporting
confidence: 65%
“…These observations are in accordance with the multiple results on NSC protection, proliferation, and differentiation both in vivo and in vitro (Table 1). Rat midbrain NSCs None Viability↑ dopaminergic differentiation (tyrosine hydroxylase↑), BDNF↑ GDNF↑ [110] Mouse NSCs from ganglionic eminence None Differentiation to neurons↑ in FBS-stimulated proliferation, but not in differentiation period [111] Murine induced pluripotent stem cells None Differentiation to NSCs↑ and further to neurons↑ PI3K/AKT signaling [112] Mouse hippocampal NSCs None Survival↑ differentiation↑ [113] NSCs from adult murine SVZ None Proliferation↑ differentiation↑; ERK/MAPK signaling [114,115] Rat adult hippocampal NSCs None Proliferation↑ phosphorylation of ERK1/2 andc-Raf [116] Mouse adult spinal cord NSPCs None Proliferation↑ PI3K/AKT signaling [117] Murine hippocampus in vivo None Neurogenesis↑ [118] Murine dentate gyrus in vivo None NeuN+ cells↑ DCX+ cells↑ [108,113,[119][120][121][122][123][124] Rat dentate gyrus in vivo Pinealectomy Neurogenesis↑ [125] Rat embryonal NSCs IL-18 Proliferation↑ differentiation↑ BDNF↑ GDNF↑ [126] Mouse embryonic cortical NSCs LPS Sox2 expression↑ PI3K/Akt/Nrf2 signaling [20] Mouse cortical NSCs in vitro Hypoxia Proliferation↑ differentiation to neurons↑ MT 1 dependence, pERK1/2↑ [19] Mouse embryonic cortical NSCs Hyperglycemia Proliferation↑ self-renewal↑ autophagy↓ [127] Murine dentate gyrus in vivo Corticosterone Attenuation of proliferation suppression [128] Rat adult hippocampal NSCs Dexamethasone Reversal of inhibition of nestin and Ki67 expression [129] Murine dentate gyrus in vivo Dexamethasone Attenuation of suppressed DCX expression [130] Murine dentate gyrus in vivo Cuprizone Restoration of Ki67+ proliferative cells and DCX+ NPCs; BNDF↑ [131] Murine dentate gyrus in vivo Scopolamine Restoration of Ki67+ proliferative cells and DCX+ NPCs [132] Murine dentate gyrus in vivo d-Galactose (aging model) Restoration of Ki67+ proliferative cells and DCX+ NPCs…”
Section: Neurogenesis From Nscs/nspcsmentioning
confidence: 99%
“…When mice were subjected to 10 mg/kg luzindole daily for 14 days, DCX+ neuronal precursor cells and Ki-67+ proliferative cells in the subgranular zone (SGZ) reduced [ 45 ]. Ex vivo studies also showed that melatonin increased survival, proliferation, and differentiation of adult SVZ, hippocampal, and spinal cord NSCs through the melatonin receptors via the ERK/MAPK and PI3K/Akt signaling pathways [ 33 , 34 , 35 , 36 , 37 ] ( Table 1 and Table 2 ).…”
Section: Roles Of Melatonin In Modulation Of Neurogenesismentioning
confidence: 99%
“…Furthermore, melatonin enhanced in vitro proliferation of neural stem cells from adult mouse spinal cord via the participation of receptors and the PI3K/Akt pathway (Yu et al, 2019). In this sense, our findings suggest that the interaction of melatonin with the MT 1 receptor and further activation of the PI3K/Akt/FOXO3a pathway is potentially involved in the maintenance of survival and stimulation of primordial follicle activation in vitro in sheep.…”
Section: Discussionmentioning
confidence: 55%